Study on the Water Invasion and Its Effect on the Production from Multilayer Unconsolidated Sandstone Gas Reservoirs - Yong Hu; Xizhe Li; Weijun Shen; Changmin Guo; Chunyan Jiao; Xuan Xu; Yuze Jia (Geofluids)
Water invasion is a common occurrence in multilayer unconsolidated gas reservoirs, which results in excessive water production and reduces the economic life of gas wells. However, due to multiple layers, active edge water, and strong heterogeneity, the mechanism of water invasion and its effect in the unconsolidated sandstone gas reservoir require understanding in order to improve efficiency and minimize economic cost. In this study, an experimental study on edge water invasion of the multilayer commingled production in unconsolidated sandstone gas reservoirs was conducted to understand the water invasion process along with different permeability layers. The results show that the edge water invasion in the commingling production is mainly affected by two major factors including reservoir permeability and gas production rate, which jointly control the encroaching water advance path and speed. The nonuniform invade of edge water may occur easily and water prefers to invade toward the gas well along with high permeability layers when the commingling production is in the condition of large permeability gradient and high production rate. The bypass flow will occur when there are high permeability channels between the layers, which causes water blocking to low-permeability layers and periphery reservoirs far away from gas wells. The findings of this study can help for a better understanding of water invasion and the effects of reservoir properties so as to optimize extraction conditions and predict gas productivity in unconsolidated sandstone gas reservoirs.